2021
DOI: 10.5812/ijhrba.108414
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of People Living with HIV (PLHIV) in Jahrom, Southern Iran: A Phenomenological Study

Abstract: Background: HIV/AIDS has remained a public health issue, especially in developing countries. The contributing factors to HIV/AIDS include poor access to medical care, fear, shame because of stigmatization, and lack of social support resulting in the isolation of people who share their status. Objectives: Taking a phenomenological descriptive approach, this qualitative study investigated the experiences of people living with HIV (PLHIV) in Jahrom, Southern Iran. Materials and Methods: The data were collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…This stigma perpetuates the notion that individuals with HIV are somehow “undesirable” as potential partners, causing them to face additional emotional and psychological challenges in their pursuit of love and companionship (Omer et al, 2014 ). The presence of stigma towards individuals living with HIV is a consistent finding across multiple phenomenological studies (Imani et al, 2021 ; Jahromy et al, 2021 ; Sadati et al, 2019 ).…”
Section: Discussionmentioning
confidence: 60%
“…This stigma perpetuates the notion that individuals with HIV are somehow “undesirable” as potential partners, causing them to face additional emotional and psychological challenges in their pursuit of love and companionship (Omer et al, 2014 ). The presence of stigma towards individuals living with HIV is a consistent finding across multiple phenomenological studies (Imani et al, 2021 ; Jahromy et al, 2021 ; Sadati et al, 2019 ).…”
Section: Discussionmentioning
confidence: 60%
“…Corroborating the research findings, the family is always identified as the main component of the social network of people living with HIV and AIDS and the main source of daily support for coping with the disease (2,(11)(12)19) , because it constitutes the first space of social coexistence in which an individual is inserted, acting in a decisive way in the other relationships (20) .…”
Section: Discussionmentioning
confidence: 91%
“…In this regard, it is important to consider that the main reason for diagnosis confidentiality was the fear of prejudice, a feeling still present in the daily life of people living with HIV and AIDS, as corroborated by the findings of other studies in the area (2,19) , which show that omission takes place in different spheres, be it in the family, socially or at work.…”
Section: Wwwscielobr/reeuspmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, global reports from The Joint United Nations Programme on HIV/ AIDS (UNAIDS) showed that by the end of 2020, 37.7 million people were living with HIV, 1.5 million people were new cases, and 680,000 people died due to AIDSrelated diseases (UNAIDS, 2020). In 2019, it is estimated that there were more than 59,000 PLHIV in Iran (Jahromy et al, 2021). Although the life expectancy of PLHIV has improved with the availability of antiretroviral therapy, PLHIV continue to experience a low level of QoL (Arjun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%